New and Old Elements of Power and Politics in the Middle East - Fares Center for Eastern Mediterranean Studies (Tufts Archival Research Center, 2015)
Occasional Paper No. 6; A report on three lectures given by the Spring 2010 Fares Center Visiting Scholar Rami G. Khouri as a part of the Fares Lecture Series.